Constructing effective questionnaires - Peterson, Robert A. (Robert Allen), 1944- (Thousand Oaks, [Calif.] : SAGE, 2000)
Asking the right questions is at the heart of all successful survey research. This text will teach students and new researchers how to commission, conduct and evaluate research based on asking these questions. The author's experience as well as in-depth knowledge of conceptual and methodological literature make this an invaluable guide for all those new to survey research.
Includes bibliographical references and indexes.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social surveys -- Methodology; Questionnaires -- Methodology